Prevalence and Spectrum of Germline BRCA1 and BRCA2 Variants of Uncertain Significance in Breast/Ovarian Cancer: Mysterious Signals From the Genome - Fanale, Daniele; Fiorino, Alessia; Incorvaia, Lorena; Dimino, Alessandra; Filorizzo, Clarissa; Bono, Marco; Cancelliere, Daniela; Calò, Valentina; Brando, Chiara; Corsini, Lidia Rita; Sciacchitano, Roberta; Magrin, Luigi; et al. (Frontiers in Oncology, 2021)
About 10-20% of breast/ovarian (BC/OC) cancer patients undergoing germline BRCA1/2 genetic testing has been shown to harbour Variants of Uncertain Significance (VUS). Since little is known about the prevalence of germline BRCA1/2 VUS in Southern Italy, our study was aimed at describing the spectrum of these variants detected in BC/OC patients in order to improve the identification of potentially high-risk BRCA variants helpful in the patient clinical management. Eight hundred and seventy-four BC or OC patients, enrolled from October 2016 to December 2020 at the “Sicilian Regional Center for the Prevention, Diagnosis and Treatment of Rare and Heredo-Familial Tumors” of University Hospital Policlinico “P. Giaccone” of Palermo, were genetically tested for germline BRCA1/2 variants through Next-Generation Sequencing analysis. The mutational screening showed that 639 (73.1%) out of 874 patients were BRCA-w.t., whereas 67 (7.7%) were carriers of germline BRCA1/2 VUS, and 168 (19.2%) harboured germline BRCA1/2 pathogenic/likely pathogenic variants. Our analysis revealed the presence of 59 different VUS detected in 67 patients, 46 of which affected by BC and 21 by OC. Twenty-one (35.6%) out of 59 variants were located on BRCA1 gene, whereas 38 (64.4%) on BRCA2. We detected six alterations in BRCA1 and two in BRCA2 with unclear interpretation of clinical significance. Familial anamnesis of a patient harbouring the BRCA1-c.3367G>T suggests for this variant a potential of pathogenicity, therefore it should be carefully investigated. Understanding clinical significance of germline BRCA1/2 VUS could improve, in future, the identification of potentially high-risk variants useful for clinical management of BC or OC patients and family members.